SP0046 Sleep as A Modulator and Adjuvant in Immunity. (15th July 2016) - Lange, T.
Abstract : Sleep and immunity are linked by bidirectional interactions. On the one hand, immune activation induces fatigue, sleepiness and non-rapid eye movement (NREM) sleep, whereas REM sleep is suppressed. On the other hand, sleep, in particular NREM sleep, regulates immune functions in an overall immunosupportive manner. Thus, NREM sleep drives the release of pro-inflammatory hormones such as growth hormone, prolactin and aldosterone at a time when anti-inflammatory hormones such as cortisol and catecholamines reach lowest levels. In healthy subjects this unique endocrine pattern during NREM sleep seems to facilitate T cell homing to lymph nodes, pro-inflammatory cytokine production by stimulated monocytes and dendritic cell precursors and vaccine-driven T and B cell responses. However, in addition to this adjuvant-like action, sleep also exerts anti-inflammatory, regulatory functions. Thus, sleep presumably counteracts sterile, low-grade systemic inflammation, shifts anti-inflammatory cytokine production of stimulated monocytes to the daytime period and supports regulatory T cell functions. In autoimmune diseases these fine-tuned interactions between sleep and immunity are distorted. Potential causes, consequences and therapeutic implications of this dysregulation will be outlined exemplarily for patients with rheumatoid arthritis, systemic lupus erythematosus and systemic sclerosis. Disclosure of Interest: None declared